Dekonstruksi Media Massa Atas Peran Perempuan: Upaya Pemberitaan Sensitif Gender - Waid, Abdul (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
Most people don't realize that recently mass media has been discrediting women. News about women by media displays them purely on physical appearance as though it had been an